Global business cycles and credit risk - Mohammad Hashem Pesaran; Til Schuermann; Björn-Jakob Treutler (Center for Economic Studies and ifo Institute (CESifo), 2005)
The potential for portfolio diversification is driven broadly by two characteristics: the degree to which systematic risk factors are correlated with each other and the degree of dependence individual firms have to the different types of risk factors. Using a global vector autoregressive macroeconometric model accounting for about 80% of world output, we propose a model for exploring credit risk diversification across industry sectors and across different countries or regions. We find that full firm-level parameter heterogeneity along with credit rating information matters a great deal for capturing differences in simulated credit loss distributions. Imposing homogeneity results in overly skewed and fat-tailed loss distributions. These differences become more pronounced in the presence of systematic risk factor shocks: increased parameter heterogeneity reduces shock sensitivity. Allowing for regional parameter heterogeneity seems to better approximate the loss distributions generated by the fully heterogeneous model than allowing just for industry heterogeneity. The regional model also exhibits less shock sensitivity.
Keywords: C32; G20; E17; 330; risk management; default dependence; economic interlinkages; portfolio choice; Kreditrisiko; Portfolio-Management; Zahlungsunfähigkeit; Unternehmenswert; Konjunkturzusammenhang; Welt